An assessment of non-muslim tourist experience at tourism mosques in Klang Valley - Maimunah Abdul Aziz (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2022)
Malaysia is an Islamic country that possess beautiful Islamic Architectural charms scattered in every region, and mosque is one of the main attractions. Mosques in Malaysia is not merely a house of worship and an Islamic institution to the Muslim community, yet it is a place to visit among non-Muslim tourists locally and internationally. This is in line with the rapid development and increasing demand for Islamic and Religious Tourism. Most importantly, mosque is an edifice that exhibit and depict the whole picture of Islam, its practice and the diverse cultures of the country. Thus, it is crucial to ensure that Tourism Mosques in Malaysia serve the best facilitation and quality service to tourists, more specifically the non-Muslims. In relation to this, the research aimed at assessing Tourism Mosques’ performance in the perspective and experience of non-Muslim tourists. In conducting the research, a sequential mix-methodology approach was applied. At the first stage, it begun with quantitative approach which sought to evaluate tourists’ satisfaction towards destination determinant attributes through questionnaire survey that were answered by 900 non-Muslim tourists at 6 Tourism Mosques. This is followed by the second stage of qualitative approach that employed hermeneutical phenomenology interview to explore and analyse non-Muslim tourists’ experiences. Statistical data gained from the questionnaire survey were analysed using SPSS Software for descriptive and inferential analyses. Meanwhile, data from semi-structured interview for phenomenology were analysed using thematic coding technique in determining new additional destination determinant attributes. Essentially, combination of data from both the research approaches attempted to develop model of determinant attributes that influence tourist experience at Tourism Mosques. The result obtained from the study had informed that the 6 Tourism Mosques is satisfying to tourists and the satisfaction model and checklist developed through the both stages of assessment is reliable and practical. As an impact, the research is expected beneficial for Tourism Mosque organisers in Malaysia to evaluate and continuously monitor their program performances through the recommended tourist satisfaction checklist. Furthermore, the result, data and recommendation could also be a reference for Islamic Tourism Centre (ITC) Malaysia, Ministry of Tourism and Culture Malaysia (MoTaC) and other tourism players to monitor and plan the better destination development strategies that are relevant to elevate Tourism Mosque’s potential.